Cadmium Inhibits Lateral Root Emergence in Rice by Disrupting OsPIN-Mediated Auxin Distribution and the Protective Effect of OsHMA3. (10th December 2020) - Wang, Han-Qing; Xuan, Wei; Huang, Xin-Yuan; Mao, Chuanzao; Zhao, Fang-Jie
Abstract: Cadmium (Cd) strongly inhibits root growth, especially the formation of lateral roots (LRs). The mechanism of Cd inhibition on LR formation in rice ( Oryza sativa ) remains unclear. In this study, we found that LR emergence in rice was inhibited significantly by 1 M Cd and almost completely arrested by 5 M Cd. Cd suppressed both the formation and subsequent development of the lateral root primordium (LRP). By using transgenic rice expressing the auxin response reporters DR5::GUS and DR5rev::VENUS, we found that Cd markedly reduced the auxin levels in the stele and LRP. Cd rapidly downregulated the expression of the auxin efflux transporter genes OsPIN1b, OsPIN1c and OsPIN9 in the stele and LRP. The emergence of LRs in a rice cultivar with a null allele of OsHMA3 ( Heavy Metal ATPase 3 ) was more sensitive to Cd than cultivars with functional alleles. Overexpression of functional OsHMA3 in rice greatly alleviated the inhibitory effect of Cd, but the protective effect of OsHMA3 was abolished by the auxin polar transport inhibitor 1- N -naphthylphthalamic acid. The results suggest that Cd inhibits LR development in rice by disrupting OsPIN-mediated auxin distribution to LRP and OsHMA3 protects against Cd toxicity by sequestering Cd into the vacuoles.